Building A 6805-compatible microcontroller using FPGA - 433236 Koh, Tat Hui (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering (Computer)) - Universiti Teknologi Malaysia, 2003